2010
DOI: 10.1094/cm-2010-1220-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Economics of Shallow Subsurface Drip Irrigation (S3 DI) and Furrow Diking

Abstract: A S3DI system was installed annually with and without furrow diking to document yield and economic benefits of these techniques on peanut (Arachis hypogaea L.), cotton (Gossypium hirsutum L.), and corn (Zea mays L.). This research was conducted for three years and each crop had four treatments replicated three times in a randomized complete block design. Treatments included irrigation, irrigation plus furrow diking, non‐irrigation, and non‐irrigation plus furrow diking. In 2005, a high precipitation year, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 15 publications
(28 reference statements)
3
29
0
Order By: Relevance
“…Irrigated and non-irrigated treatments were included. Irrigation in 2012 was done with shallow sub-surface drip (which has shown no yield difference from overhead sprinkler) and overhead sprinkler was used in 2013 and 2014 (Sorensen et al, 2010). Planting dates were 17 April 2012, 26 April 2013, and 24 April 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Irrigated and non-irrigated treatments were included. Irrigation in 2012 was done with shallow sub-surface drip (which has shown no yield difference from overhead sprinkler) and overhead sprinkler was used in 2013 and 2014 (Sorensen et al, 2010). Planting dates were 17 April 2012, 26 April 2013, and 24 April 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research (Sorensen and Lamb, 2008, 2009) has shown that surface drip irrigation (SDI) can be installed with low initial investment and labor, be used on a variety of crops, and increase crop yield compared with nonirrigated areas. Burying the drip tubing 1.5 to 2 inches below the soil surface (shallow subsurface drip irrigation– S 3 DI) can significantly reduce rodent damage (Sorensen et al, 2010). Yield potential of irrigated crops using S 3 DI was over two, three, and seven times greater than nonirrigated crops of peanut, cotton, and corn, respectively, depending on yearly precipitation timing and amount (Sorensen et al, 2010).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Burying the drip tubing 1.5 to 2 inches below the soil surface (shallow subsurface drip irrigation– S 3 DI) can significantly reduce rodent damage (Sorensen et al, 2010). Yield potential of irrigated crops using S 3 DI was over two, three, and seven times greater than nonirrigated crops of peanut, cotton, and corn, respectively, depending on yearly precipitation timing and amount (Sorensen et al, 2010). The increased yield and eventual gross revenue were great enough in the installation year to cover the cost of the in‐field portion of the S 3 DI system expenses compared with the nonirrigated revenue (Sorensen et al, 2010).…”
Section: Useful Conversionsmentioning
confidence: 99%
See 2 more Smart Citations